Effects of Phenanthrene Exposure on Cholesterol Homeostasis and Cardiotoxicity in Zebrafish Embryos. (23rd March 2021) - McGruer, Victoria; Tanabe, Philip; Vliet, Sara M.F.; Dasgupta, Subham; Qian, Le; Volz, David C.; Schlenk, Daniel
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are pervasive pollutants in aquatic ecosystems, and developing fish embryos are especially sensitive to PAH exposure. Exposure to crude oil or phenanthrene (a reference PAH found in oil) produces an array of gross morphological abnormalities in developing fish embryos, including cardiotoxicity. Recently, studies utilizing transcriptomic analyses in several oil‐exposed fish embryos found significant changes in the abundance of transcripts involved in cholesterol biosynthesis. Given the vital role of cholesterol availability in embryonic heart development, we hypothesized that cholesterol dysregulation in early development contributes to phenanthrene‐induced cardiotoxicity. We exposed zebrafish embryos to 12 or 15 µM phenanthrene from 6 to 72 h post fertilization (hpf) and demonstrated that, in conjunction with pericardial edema and bradycardia, several genes ( fdft1 and hmgcra ) in the cholesterol biosynthetic pathway were significantly altered. When embryos were pretreated with a cholesterol solution from 6 to 24 hpf followed by exposure to phenanthrene from 24 to 48 hpf, the effects of phenanthrene on heart rate were partially mitigated. Despite changes in gene expression, whole‐mount in situ staining of cholesterol was not significantly affected in embryos exposed to phenanthrene ranging in stage from 24 to 72 hpf. However, the 2‐dimensional yolk area was significantly increased with phenanthrene exposure at 72 hpf, suggesting that lipid transport from the yolk to the developing embryo was impaired. Environ Toxicol Chem 2021;40:1586–1595. © 2021 SETAC